Integrated assessment of wastewater treatment plant effluent estrogenicity in the Upper Murray River, Australia, using the native Murray rainbowfish (Melanotaenia fluviatilis). (7th April 2015) - Vajda, Alan M.; Kumar, Anupama; Woods, Marianne; Williams, Mike; Doan, Hai; Tolsher, Peter; Kookana, Rai S.; Barber, Larry B.
Abstract: The contamination of major continental river systems by endocrine‐active chemicals (EACs) derived from the discharge of wastewater treatment plant (WWTP) effluents can affect human and ecosystem health. As part of a long‐term effort to develop a native fish model organism for assessment of endocrine disruption in Australia's largest watershed, the Murray‐Darling River Basin, the present study evaluated endocrine disruption in adult males of the native Australian Murray rainbowfish (Melanotaenia fluviatilis) exposed to effluent from an activated sludge WWTP and water from the Murray River during a 28‐d, continuous‐flow, on‐site experiment. Analysis of the WWTP effluent and river water detected estrone and 17β‐estradiol at concentrations up to approximately 25 ng L −1 . Anti‐estrogenicity of effluent samples was detected in vitro using yeast‐based bioassays (yeast estrogen screen) throughout the experiment, but estrogenicity was limited to the first week of the experiment. Histological evaluation of the testes indicated significant suppression of spermatogenesis by WWTP effluent after 28 d of exposure. Plasma vitellogenin concentrations and expression of vitellogenin messenger RNA in liver were not significantly affected by exposure to WWTP effluent. The combination of low contaminant concentrations in the WWTP effluent, limited endocrine disrupting effects in the Murray rainbowfish, and high in‐stream dilution factors (>99%) suggest minimal endocrine disruption impacts on native Australian fish in the Murray River downstream from the WWTP outfall. Environ Toxicol Chem 2015;34:1078–1087. © 2015 SETAC